Are cities venturing green? A global analysis on the impact of green entrepreneurship on city air pollution - Cojoianu, T; Hoepner, AGF; Hu, X; Ramadan, M; Veneri, P; Wojcik, D (Springer Nature, 2023)

(untitled)
Situated at the intersection between environmental entrepreneurship and urban sustainability, our paper seeks to investigate the links between city-level green venture ecosystems and the ability of urban centres to reduce air pollution. Using a large dataset of 12,834 urban centres from around the world and their associated yearly average particulate matter (PM2.5), we show that an increase in the cumulative number of green start-ups drives the lowering of PM2.5 levels. Looking closely at the subsectors that drive the results, we observe that the urban centres which hosted increased numbers of innovators in smart grid technologies, energy efficiency and wind energy generation (the low carbon energy sector overall) also experienced a decrease in air pollution over the 2010–2019 period. Thus, our study is a global analysis of the environmental impact of green entrepreneurship on local air pollution.